THE USE OF VERBAL REPERTOIRE IN THE HUMAN STATUS AS THE IMAGO DEI AND GOD’S KINGDOM COMMUNITY - Jonter Pandapotan Sitorus (Jurnal Theologia Forum STFT Surya Nusantara, 2019)
Originally, Christians are created according to God’s image - imago dei – which indicates that God’s attributes also live and exist in the life of His people. Furthermore, while living here on earth, Christians have two status. The First is the status as a citizen in this world. The Second is the status as the citizen of the Kingdom of God. As this world’s citizen, human beings have rights and responsibilities toward the government in which they live. Their citizenship has been arranged according to the rule of the specific country. As the citizen of the Kingdom of Godthrough the grace of God that has chosen His people, human beings have to pay attention to their communication ability especially the ability to use the language and its variations, known as verbal repertoire. The usage of verbal repertoire is expected to glorify God in the communication individually and collectively as a community. Moreover, human beings, as imago dei and the people of God’s Kingdom, have to use verbal repertoire to be a blessing for other people and draw to God those who live far from Him through their verbal testimonies. Key words: Imago Dei, verbal repertoire, people of the Kingdom of God.